Unpacking disciplinary literacies through CLIL teachers' perspectives across Science, Social Science and Mathematics in Europe - Nashaat-Sobhy, Nashwa; Duman, Saime Kara; Huttner, Julia; Mortimore, Louisa; Kaygisiz, Semih; Roseni, Emilda; Bayyurt, Yasemin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
The nature and development of bi- and multilingual disciplinary literacies (BMDL) have become an increasingly critical area of inquiry in multilingual educational contexts such as CLIL. This study examines how CLIL teachers conceptualise subject-specific literacies through semi-structured interviews with 13 science, social science and mathematics teachers in Albania, Austria, Spain and Turkey. Drawing on the five BMDL dimensions developed within CLILNetLE (www.clilnetle.eu) and inductively derived themes, the analysis shows that teachers viewed learning subject content and learning to reason, communicate, and represent knowledge as mutually dependent processes. Content-area literacy practices were described as coexisting with disciplinary literacy practices, emphasising the plurality of literacies at play. Teachers characterised their subjects in ways consistent with disciplinary literacy research and linked students' development to cognitive and linguistic maturity. The findings clarify how BMDL dimensions operate distinctly yet interdependently: the functional dimension, realised through genres and cognitive discourse functions, seems to act as the core driver of disciplinary reasoning; the multilingual and multisemiotic dimensions function as linguistic and representational vehicles; the critical dimension signals depth of reasoning; and the technological dimension serves as an enabling environment. The study foregrounds teachers' perspectives as essential for refining the conceptualisation of BMDL.
Keywords: CLIL; disciplinary literacies; secondary education; primary education; teacher beliefs; semi-structured interviews; Linguistics